Conflict of the Main Characters in Steel’s Silent Honor - Ramajaya, I Made Aditya; Mulyawan, I Wayan; partama, I Gusti Ngurah (e-Journal of Linguistics; Vol 16 No 1 (2022): ejl-JanuaryDO - 10.24843/e-jl.2022.v16.i01.p06, 2021)
This study aims to determine the psychological conflict "Hiroko" as the main character in Steel's Silent Honor story. The data of this study are taken from the story "Silent Honor" by Danielle Steel through the documentation method and note-taking technique. The data were analysed qualitatively by two major theories applied in this study:  literary theory and psychological theory. The data are presented in a descriptive narrative according to the adapted theory to get a conclusion. The result showed that psychologically, Hiroko has the basic needs of an ordinary human. She needs kind and respectful treatment from those around him, especially from Americans. Furthermore, all aspects of motivation such as appetite, desire, emotions, feelings and attitudes make Hiroko's personality more complete. This motivational aspect is what makes her a hard worker and an independent girl.